Highlights of recent IFPRI food policy research for Latin America and the Caribbean: Reducing poverty and hunger through food policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
For more than 30 years, IFPRI’s research and collaboration in Latin America and the Caribbean have contributed to positive changes in the region, including enhancing the culture of accountability and generating groundbreaking evidence that has strengthened resilience, improved nutrition, and spurred strategic food security policies and investments. Moreover, IFPRI’s work in the region helped strengthen the capacity of policy makers, development practitioners, and stakeholders to conduct sound evaluations, data analysis, and economic modeling. IFPRI’s work has led to economic and nutritional improvements in Brazil, Guatemala, Mexico, and Nicaragua, with lessons that even spill over to Africa. Moving forward, the region faces the challenges of poverty, high rates of undernutrition, economic inequality, climate change, and inadequate public investments. To accelerate progress, IFPRI will continue to engage stakeholders from various interrelated sectors (including agriculture, finance, nutrition, research, and social protection) in Latin America and the Caribbean to promote evidencebased policy making and investments to ensure improved livelihoods, poverty alleviation, and food and nutrition security.